2013
DOI: 10.1071/zo12122
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in vigilance in female eastern grey kangaroos

Abstract: For herbivores, vigilance usually involves a trade-off with foraging, and a further trade-off between antipredator and social vigilance. Thus individual variation in vigilance may result in significant fitness consequences. We used mixed-effects models to document individual variation in vigilance in wild adult female eastern grey kangaroos (Macropus giganteus) in Queensland, Australia. We tested the effects of group size, presence of adult males and wind on vigilance patterns and variation by analysing 399 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Type C, in which vigilance decreases more rapidly with group size for individuals facing high risk, was not expected and indeed was only found in a few cases. In one such case, female eastern grey kangaroos ( Macropus giganteus ) decreased their vigilance in larger groups more rapidly when facing threats from males (Dannock, Blomberg, & Goldizen, ), suggesting that males might be more threatening when females are in small groups. Unexpected results such as this should spur the development of social vigilance models.…”
Section: Discussionmentioning
confidence: 99%
“…Type C, in which vigilance decreases more rapidly with group size for individuals facing high risk, was not expected and indeed was only found in a few cases. In one such case, female eastern grey kangaroos ( Macropus giganteus ) decreased their vigilance in larger groups more rapidly when facing threats from males (Dannock, Blomberg, & Goldizen, ), suggesting that males might be more threatening when females are in small groups. Unexpected results such as this should spur the development of social vigilance models.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between females have been shown to be non-random , with some females having preferred associates (Best, Dwyer, Seddon, & Goldizen, 2014;Carter, MacDonald, Thomson, & Goldizen, 2009), showing that females differ in their patterns of sociability. In addition, between-individual variation in vigilance has been previously described (Carter, Pays, et al 2009;Dannock, Blomberg, & Goldizen, 2013) and related to boldness in eastern grey kangaroos, tending to support the behavioural hypothesis . Ecological drivers and individuals' characteristics such as group size, patch attractiveness and reproductive states have also been reported to shape feeding rates and/or vigilance in this species (e.g.…”
Section: Introductionsupporting
confidence: 53%
“…My MSc research showed that the absence of variation in total vigilance with group size in some studies of this species could be explained by the combination of a decrease in anti-predator vigilance and an increase in social vigilance as group size increases . Recent studies showed the existence of significant differences among individuals in eastern grey kangaroos' mean vigilance levels and in their adjustment of vigilance as group size increased (Carter et al 2009a, Dannock et al 2013. In their study, Carter et al (2009a) revealed that, among the same population, different females decreased, increased or did not exhibit any variation in their vigilance levels as group size increased.…”
Section: -2-1 Eastern Grey Kangaroosmentioning
confidence: 98%
“…Recent studies have shown individual variation in vigilance behavior (Boujja‐Miljour et al., 2018; Dannock et al., 2013; Favreau et al., 2014; Rieucau et al., 2010). However, few studies have looked at the relationship between predator density, vigilance, and individual variation in vigilance behavior.…”
Section: Discussionmentioning
confidence: 99%